SCF (Stem Cell Factor) and cKIT modulate pathological ocular neovascularization - Kim, Koung Li; Seo, Songyi; Kim, Jee Taek; Kim, Jaetaek; Kim, Won; Yeo, Yeongju; Sung, Jong Hyuk; Park, Sang Gyu; Suh, Wonhee (Arteriosclerosis, Thrombosis, and Vascular Biology, 2019)
Objective: Aberrant neovascularization is a leading cause of blindness in several eye diseases, including age-related macular degeneration and proliferative diabetic retinopathy. The identification of key regulators of pathological ocular neovascularization has been a subject of extensive research and great therapeutic interest. Here, we explored the previously unrecognized role of cKIT and its ligand, SCF (stem cell factor), in the pathological ocular neovascularization process. Approach and Results: Compared with normoxia, hypoxia, a crucial driver of neovascularization, caused cKIT to be highly upregulated in endothelial cells, which significantly enhanced the angiogenic response of endothelial cells to SCF. In murine models of pathological ocular neovascularization, such as oxygen-induced retinopathy and laser-induced choroidal neovascularization models, cKIT and SCF expression was significantly increased in ocular tissues, and blockade of cKIT and SCF using cKit mutant mice and anti-SCF neutralizing IgG substantially suppressed pathological ocular neovascularization. Mechanistically, SCF/cKIT signaling induced neovascularization through phosphorylation of glycogen synthase kinase-3β and enhancement of the nuclear translocation of β-catenin and the transcription of β-catenin target genes related to angiogenesis. Inhibition of β-catenin-mediated transcription using chemical inhibitors blocked SCF-induced in vitro angiogenesis in hypoxia, and injection of a β-catenin agonist into cKit mutant mice with oxygen-induced retinopathy significantly enhanced pathological neovascularization in the retina. Conclusions; Our data reveal that SCF and cKIT are promising novel therapeutic targets for treating vision-threatening ocular neovascular diseases.
Keywords: Analysis of Variance; Angiogenesis Inhibitors; Animals; Cells, Cultured; Disease Models, Animal; Endothelial Cells; Enzyme-Linked Immunosorbent Assay; Female; Gene Expression Regulation; Humans; Hypoxia; Immunohistochemistry; Male; Mice; Mice, Inbred C57BL; Proto-Oncogene Proteins c-kit; Retinal Diseases; Retinal Neovascularization; Signal Transduction; Stem Cell Factor; Vascular Endothelial Growth Factor A; Angiogenesis; Catenin; cKIT; Endothelial cell; Hypoxia; Stem cell factor